Understanding the crucial impact of deregulated autophagy & lysosomal stress in diffuse parenchymal lung diseases - Mahavadi, Poornima; Justus Liebig University Giessen (My University, 2021)
The data provided in this work strongly support the concept that alterations in the autophagy-lysosomal system contribute to alveolar epithelial cell injury and apoptosis, representing a key trigger in the development of lung fibrosis. Altered surfactant homeostasis in HPSIP and AD induced lung fibrosis, in addition to the previous reports in IPF lungs, were first indicators of an effect on the lysosomal compartment of AECII. Further evidence for lysosomal stress stems from the observation of increased markers of autophagy in IPF patient lungs and HPSIP as well as in the AD models of lung fibrosis. One discrepancy that we reported is, however, that autophagic activity is increased under conditions of amiodarone treatment, while it is impaired in HPS associated lung fibrosis. Such defective autophagy has also been reported in AECII of IPF patient lungs. This indicates that, depending on the type, level and mode of insult, autophagy is differentially regulated in different models of lung fibrosis. The same holds true for the unfolded protein response: both, too little and too intensive (pro-apoptotic) ER stress might be detrimental for the cell. In addition, enhanced ER stress signatures as well as oxidative stress, indicative of mitochondrial dysfunction add another level of complexity to our understanding of the epithelial injury in the evolution of fibrotic diseases. It is known that, despite being discrete signalling components, these cellular organelles play a concerted role to maintain cellular homeostasis in response to any insult. In aging lungs like IPF, or in lungs with a genetic predisposition like HPSIP or in lungs affected by drugs like AD, such organelle crosstalk is disrupted creating an imbalance, which might fuel common cell death mechanisms. The immediate next steps will be aimed at understanding if pharmacological correction of autophagy-lysosomal system, eg., by autophagy inducing drugs, would be beneficial in rescuing the fibrotic AECII from toxic proteins and to re-direct them to pro-survival programs. That said, the indubitable role of other cellular compartments like the ER or mitochondria in the process of epithelial injury and lung fibrosis underscores the need for further research, aiming to identify molecular machineries coordinating organelle crosstalk in injured AECII and to develop novel molecular switches affecting all of these surveillance programs.
Verständnis der entscheidenden Auswirkungen von deregulierter Autophagie und lysosomalem Stress bei diffusen parenchymalen Lungenerkrankungen
Keywords: autophagy; aging; lung fibrosis; diffuse parenchymal lung diseases; chronic lung diseases; alveolar epithelial cells; fibroblasts; apoptosis; ddc:570; ddc:610